Survey and analysis of public knowledge, awareness and willingness to pay in Kuala Lumpur, Malaysia - a case study on household WEEE management - Rafia, Afroz; Masud, Muhammad Mehedi; Akhtar, Rulia; Duasa, Jarita (Elsevier Inc., 2013)
The main objective of this study is to evaluate public knowledge and awareness about the impact of waste from electrical and electronic equipment (WEEE) on health and environment, their willingness to pay (WTP) for improving WEEE management in Kuala Lumpur, the household electric and electronic equipment’s (EEE) product lifetime, the reasons to update, and the deposit and disposal processes of WEEE, and to discuss these results within the context of proper management of WEEE. The data and information used in this study were collected by distributing questionnaires randomly in 5 residential areas in Kuala Lumpur, and interviewing 350 households. The results indicate that the majority of the households (59%) have knowledge about the environmental and health impacts of WEEE. More than half of the households (65%) stated that they considered the environmental factors when they purchased EEE for domestic use. Unfortunately, despite their knowledge about WEEE, only between 2% and 3% of the households were involved in the recycling of their WEEE. However, 52.5% of the households were willing to pay for improving WEEE management system in Kuala Lumpur. This study suggested that the government could manage the WEEE by passing effective legislations; setting up convenient collection centers for proper disposal of WEEE; and organizing campaigns, seminars and workshops to increase the level of awareness of the households and to motive them to recycle their WEEE.